How International Are Undergraduate Political Science Programs at Liberal Arts and Sciences Colleges and Universities in the Midwest? - Ishiyama, John; Breuning, Marijke (PS: Political Science & Politics, 2006)
A study was conducted to explore the extent to which the political science curricula at Midwestern undergraduate institutions are internationalized. Data were obtained from the curricula of 189 liberal arts and sciences universities and colleges in 10 Midwestern states. Findings revealed that the majority of programs required that political science students take only a minimal number of courses in international relations (IR) or comparative politics and that 29 did not require students to take any international courses. Findings also indicated that the presence of an IR or International Studies major neither enhanced nor detracted from the international content of institutions' political science major.